2019
DOI: 10.14715/cmb/2019.65.6.2
|View full text |Cite
|
Sign up to set email alerts
|

Antitumoral activity of Ficus carica L. on colorectal cancer cell lines

Abstract: In traditional medicine, Ficus carica (also known as fig) latex is recognized as a remedy with various therapeutic effects. In the present study we investigated the antitumor activity of Ficus carica extracts and latex. We evaluated the effects of increasing concentrations of Ficus carica extracts and latex on HCT-116 and HT-29 human colorectal cell proliferation using MTT assay and apoptosis induction by evaluating PARP cleavage by Western blot analysis. Peel, pulp, leaves, whole fruit and latex extracts of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 36 publications
(38 reference statements)
0
18
0
Order By: Relevance
“…Boyacioglu et al demonstrated the cytotoxicity of n-hexane extracts of the dried leaves of two fig cultivars in PC3 human prostate cancer cells [20]. Soltana et al investigated the antitumor activity of F. carica extracts (peel, pulp, leaves, whole fruit) and latex on HCT-116 and HT-29 human colorectal cells and found that the extracts and latex have antiproliferative effects and induce apoptosis in cancer cells [21]. Purnamasari et al examined the anticancer activity of F. carica leaf and fruit methanolic extracts using Huh7it liver cancer cells and their studies revealed a higher percentage of Huh7it apoptosis and necrosis in leaf extracts than in fruit extracts [22].…”
Section: Introductionmentioning
confidence: 99%
“…Boyacioglu et al demonstrated the cytotoxicity of n-hexane extracts of the dried leaves of two fig cultivars in PC3 human prostate cancer cells [20]. Soltana et al investigated the antitumor activity of F. carica extracts (peel, pulp, leaves, whole fruit) and latex on HCT-116 and HT-29 human colorectal cells and found that the extracts and latex have antiproliferative effects and induce apoptosis in cancer cells [21]. Purnamasari et al examined the anticancer activity of F. carica leaf and fruit methanolic extracts using Huh7it liver cancer cells and their studies revealed a higher percentage of Huh7it apoptosis and necrosis in leaf extracts than in fruit extracts [22].…”
Section: Introductionmentioning
confidence: 99%
“…Another study on the effect papaya leaves on breast cancer cells for antiproliferative activity showed a decrease of NF-kB. The presence of flavonoids in papaya extracts caused the reduction of RO3 which impacted the MCF-7, BCL-2, BCL-XL that in turn inhibited the proliferation of breast cancer cell lines (MCF-7) [34][35][36][37][38][39][40]. This is in accordance with the present study stating that Carica seed extract has inhibited the expression of inhibitory kappa B kinase beta expression in lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…FCL. was shown to improve diabetes and inhibit tumor cell proliferation ( Umar et al, 2013 ; Soltana et al, 2019 ; Zhang et al, 2019 ) and has known antioxidant, anti-inflammatory, and antiapoptotic effects ( Ali et al, 2012 ; Umar et al, 2013 ; Melisa et al, 2014 ; Zhang et al, 2019 ). We found here that FCL.…”
Section: Discussionmentioning
confidence: 99%